ASSISTING TEACHERS IN DESIGNING SOMATIC AUDITORY VISUAL INTELLECTUAL (SAVI) LEARNING MODEL - Arbis Arbis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the finding that the learning process between teachers and students occurred in one way directions. It was also initiated by the lack of learning that build students' abilities, skills, and creativity. By assisting the teachers, it was hoped that they would be able to design effective learning in order to make students active in the learning process, one of which was somatic, auditory, visual, and intellectual (SAVI) learning. This research was a school action research involving stages of planning, implementing, observing, and reflecting. This research was conducted to 6 teachers of SDN 009 Teluk Kiambang. The instrument used was the observation sheet. The results showed that in the first cycle the teacher's ability was 65.83 with Sufficient category while in the second cycle, it increased to 79.16, which was in Good category. Based on the results of the study, it was concluded that the ability of teachers at SDN 009 Teluk Kiambang to develop SAVI learning model increased after getting the assistance from the principal as a researcher.